THEORETICAL STUDY OF THE POTENTIAL ANTI-CHAGASIC PHARMACOLOGICAL TOOL MACHILIN G: A STUDY OF MOLECULAR DOCKING - da Silva de Almeida, Victor; de Oliveira, Victor Moreira; de Morais Filho, Carlos Lacerda; da Silva Mendes, Francisco Rogênio; da Fonseca, Aluísio Marques; Silva Marinho, Emmanuel (International Journal of Research -GRANTHAALAYAH, 2020)
Chagas disease caused by Trypanosoma cruzi, which affects thousands of people around the world. In recent years, research aimed at the discovery of new drugs has started to seek specific macromolecular targets for the disease. In this context, enzymes are therapeutic targets of great interest, since they play a fundamental role in many diseases. In this context, the present work aimed to characterize the Machilin G molecule conformationally and evaluate its interactions in the main therapeutic targets involved in the replication of T. cruzi. To understand the inhibitory mechanism of Machilin G on the evolutionary forms of T. cruzi, the molecule it was conformationally characterized, until reaching thermodynamic stability, and then it was submitted to molecule docking routines, having as protein targets the Cruzain enzymes, Tripanothione reductase and glyceraldehyde-3-phosphate dehydrogenase (TcGAPDH). Machilin G had its structure optimized using semi-empirical quantum calculations, through this technique it was possible to generate the thermodynamically more stable conformation. Through the method of analysis of the computer simulations of molecular anchoring, it was demonstrated that the ligand Machilin G was coupled to the active site of the enzyme TcGAPDH, at distances close to the chalepin. In relation to Cruzain, it is possible to highlight that the ligand Machilin G does not interact with the amino acids of the active site of the enzyme, being at a considerable distance in relation to the ligand KB2. Regarding the enzyme Trypanothione reductase, the ligand Machilin G had few interactions with the amino acids of the active site. The intermolecular interactions found for the complex formed and the values obtained at a distance from the enzyme residues indicate that Machilin G has potential application as a new inhibitor of the enzyme Trypanosoma cruzi TcGAPDH. The present work being a fundamental step for the understanding of Machilin G mechanism of action in view of the evolutionary forms of the t-cruzi parasite.